6(-2y-16)-2y=-12

Simple and best practice solution for 6(-2y-16)-2y=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-2y-16)-2y=-12 equation:


Simplifying
6(-2y + -16) + -2y = -12

Reorder the terms:
6(-16 + -2y) + -2y = -12
(-16 * 6 + -2y * 6) + -2y = -12
(-96 + -12y) + -2y = -12

Combine like terms: -12y + -2y = -14y
-96 + -14y = -12

Solving
-96 + -14y = -12

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '96' to each side of the equation.
-96 + 96 + -14y = -12 + 96

Combine like terms: -96 + 96 = 0
0 + -14y = -12 + 96
-14y = -12 + 96

Combine like terms: -12 + 96 = 84
-14y = 84

Divide each side by '-14'.
y = -6

Simplifying
y = -6

See similar equations:

| 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y | | 10=-x+2y | | 2x-18=9x+6 | | 7.57x+22.71=45.42 | | 5+3t-3=8t+14-3t | | (X+14)=(x-20) | | 25=2(x+3) | | 2x+2(x-28)=-104 | | 2x-1-x=9x-3 | | -18+10=-17s | | (x+4)(x-4)=4 | | 5+y=0.0024x | | 3x+2(x-28)=-104 | | y=3x^2-6x+200 | | 2x-8(2x-8)=44 | | 25u+75=23u+92 | | (X+10)=(x-11) | | -7-0.83x=18 | | 4x+b=ax+9 | | (X-11)=(2x-42) |

Equations solver categories